Aberrant expression of SPAG6 and NM23 predicts poor prognosis of human osteosarcoma - Bao, Zhengqi; Zhu, Ruizhi; Fan, Huagang; Ye, Yuchen; Li, Tian; Chai, Damin (Frontiers in Genetics, 2022)
Objective: To investigate the expression and clinical significance of sperm-associated antigen 6 and NM23 proteins in human osteosarcoma. Methods: The specimens of conventional osteosarcoma with follow-up from 42 Chinese patients were analyzed in this study, and 12 cases of osteochondroma were considered controls. The expression of SPAG6 and NM23 was inspected using immunohistochemical staining, qRT-PCR, and Western blotting methods. Results: The positive expression rate of SPAG6 protein (71.43%) in 42 cases of osteosarcoma tissue was significantly higher than that (33.33%) in 12 cases of osteochondroma tissues (p < 0.05), while the positive rate of NM23 protein (35.71%) in osteosarcoma tissue was lower than that (58.33%) in osteochondroma tissue (p < 0.05). The mRNA and protein levels of SPAG6 were significantly higher than those of the adjacent normal tissues, while the expression of NM23 was lower in osteosarcoma tissues than that in the controls (p < 0.05 for all). There was a positive relationship between the expression of SPAG6 and pathological grade, metastasis, and Enneking stage (p < 0.05 for all). The overall survival rate of osteosarcoma patients with SPAG6 positive expression was significantly lower than that with SPAG6 negative expression. The relationship between the expression of NM23 and pathological grade, metastasis, and Enneking stage was negative (p < 0.05 for all). The overall survival rate of the osteosarcoma patients with NM23 positive expression was higher than that of the patients with NM23 negative expression (p < 0.05). Conclusion: Overexpression of SPAG6 and low expression of NM23 are negatively related to pathological grade, metastasis, and Enneking stage and prognosis of osteosarcoma patients. This suggested that SPAG6 and NM23 should be considered candidate prognostic biomarkers for patients with osteosarcoma.